Differences in Understanding the Concept of Child Education in Islam Based on Educational Background - Ananda Bella Risdiansyah; Aulia Khoirunnisa; Nena Nabila; Nina Latipah Sanusi; Lisa Ernawasih (Penerbit Presisi Pustaka, 2026)
This study aims to understand the differences in teachers' understanding of the concept of Islamic education for children based on their educational background. The study was conducted in ten Early Childhood Education (PAUD) institutions in Jayakerta District, Karawang Regency, involving twenty teachers, consisting of twelve teachers with a bachelor's degree (PIAUD) and eight teachers without a bachelor's degree. The method used was a qualitative approach with a descriptive design, while data collection techniques were conducted through in-depth interviews. The results showed that teachers with a bachelor's degree tended to have a more systematic conceptual understanding and were able to integrate Islamic values ​​into teaching and learning activities with a planned pedagogical approach. Meanwhile, teachers without a bachelor's degree had a strong understanding in daily practice, emphasizing role models, habituation, and direct experience in instilling Islamic values ​​in children. Both groups of teachers contributed significantly to realizing Islamic values-based early childhood education. The synergy between theoretical understanding and practical experience is a key strength in the implementation of Islamic education in PAUD.